The role of paranasal sinuses in the mysterious etiopathogenesis of idiopathic scoliosis (Annals of Medical Research, 2024)
Aim: The paranasal sinuses play a role in maintaining postural balance and synthesizing neurotransmitters such as nitric oxide (NO). Although the etiopathogenesis of idiopathic scoliosis (IS) is not fully known, it is known that hormonal and neurosensory mechanisms play a role. In this study, the possible effects of paranasal sinuses on the etiology of IS were investigated.Materials and Methods: In this cross-sectional planned study, 38 individuals with IS (28 women and 10 men) and 39 healthy individuals (28 women and 11 men) were included. The right and left maxillary, sphenoid and frontal-ethmoid sinus volumes of the groups were calculated from magnetic resonance images. In addition, the entire head volume of each participant was calculated and the volume ratios occupied by all paranasal sinuses were calculated.Results: In the IS group, the right maxillary sinus mean volume decreased by 16% and the left maxillary sinus volume value decreased by 14% compared to the control group (p0.05). It was observed that the values of left maxillary sinus volume, frontal-ethmoid sinus volume, right maxillary sinus ratio, left maxillary sinus ratio and frontal-ethmoid sinus ratio were lower in male individuals in the IS group than in healthy individuals (p
Keywords: Paranasal sinus; Nitric oxide; Idiopathic scoliosis; Magnetic resonance